The effect of green transformational leadership on service employees in Indonesia / Deni Juliyando and Asep Rokhyadi Permana Saputra - Juliyando, Deni; Permana Saputra, Asep Rokhyadi (UiTM Press, 2023)
The purpose of this study was to analyse the effect of green transformational leadership on green creativity, green intrinsic motivation, and green extrinsic motivation on green creativity in service companies in Indonesia. This research method uses validity test analysis tools and reliability tests with the SmartPLS Version 3.0 program. Based on the Variance Based Structural Equation Modelling (SEM) approach. This research was conducted at a state-owned enterprise service company in Jogjakarta Province - Indonesia. Respondents in this study amounted to 119 people, with a saturated sample method, and the sampling technique used double sampling. The results show that green transformational leadership has no effect on green creativity, green transformational leadership increases and is significant on green intrinsic motivation, green intrinsic motivation influences green creativity, green intrinsic motivation partially mediates transformational leadership on green creativity, and green extrinsic motivation moderates the effect of motivation green intrinsic to green creativity.